"Our Own Foods as a Healing": The Role of Health in the Native American Food Sovereignty Movement. Issue 2 (24th January 2022) - Hoover, Elizabeth
Abstract: A wealth of literature has emerged over the past two decades exploring the need for food sovereignty activism to relocalize food production power, promote economic justice, and support more environmentally friendly means of producing food and getting it on the table. What has been less explored is the role of health in the desire to promote food sovereignty. First laying out the history of colonization on Native North American food systems, and then tracing the disease patterns that have emerged from this history, this essay ultimately explores how notions of health motivate and drive Native chefs and farmers who describe themselves as working toward food sovereignty for their communities. Drawing on interviews with members of Native American community‐based farming, gardening, and seed‐saving projects, Native chefs, as well as participation in food sovereignty summits, conferences, and cooking events, this essay illustrates the ways in which actors in the Native American food sovereignty movement are revitalizing, reclaiming, restoring, and perpetuating traditional food systems to promote good physical, cultural, and spiritual health.